Development of the Seuramoe Saentia Model Based on Acehnese Culture for Science Literacy of Madrasah Ibtidaiyah Students - Sari, Rita; Maksudin, Maksudin; Ibrahim, Ibrahim; Mardianto, Mardianto; Sapri, Sapri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aimed to develop and test the effectiveness of the Seuramoe Saentia model, a culture-based science learning model integrating Acehnese local wisdom into ecosystem instruction at the Madrasah Ibtidaiyah level. The research employed a Research and Development (R&D) approach using the ADDIE framework (Analyse, Design, Develop, Implement, Evaluate). The population consisted of 80 fifth-grade students at MIN 2 Langsa, Aceh Province, Indonesia. The implementation phase involved one experimental class comprising 25 students, selected through purposive sampling. The model was designed to integrate the traditional seuneubok land management system into science literacy learning through five instructional phases: Cultural Orientation, Context Exploration, Knowledge Construction, Artefact Creation, and Global Reflection and Expansion. Data were collected through expert validation sheets, observation instruments, science literacy tests, and documentation. Qualitative data were analyzed using thematic analysis, while quantitative data were analyzed using descriptive statistics, N-Gain calculations, and paired-sample t-tests to determine learning effectiveness. Expert validation confirmed that the model was conceptually valid, culturally relevant, and pedagogically feasible. The effectiveness results showed a significant improvement in students’ science literacy. The mean pre-test score of 61.8 increased to 79.4 in the post-test, with an N-Gain of 0.46 (moderate category). Statistical analysis indicated a significant difference between pre- and post-test scores (t = 5.37; p < 0.05). Additionally, observational findings revealed enhanced ecological awareness, collaborative skills, and the ability to connect scientific concepts with local cultural values. These findings demonstrate that integrating Acehnese cultural practices into science learning effectively improves students’ science literacy while strengthening contextual ecological understanding. The Seuramoe Saientia model offers a validated and empirically supported framework for culturally responsive science education at the primary level.